Thermal noise influences fluid flow in thin films during spinodal dewetting - Mecke, Klaus; et al. (Physical Review Letters, 2007)
Experiments on dewetting thin polymer films confirm the theoretical prediction that thermal noise can strongly influence characteristic time scales of fluid flow and cause coarsening of typical length scales. Comparing the experiments with deterministic simulations, we show that the Navier-Stokes equation has to be extended by a conserved bulk noise term to accomplish the observed spectrum of capillary waves. Because of thermal fluctuations the spectrum changes from an exponential to a power law decay for large wave vectors. Also the time evolution of the typical wave vector of unstable perturbations exhibits noise-induced coarsening that is absent in deterministic hydrodynamic flow.